COMMUNITY CHARACTERISTICS AND CONTRIBUTION LEVEL OF AGRO-FORESTRY ACTIVITIES ON INCOME OF HOUSEHOLDS IN BA VI COMMUNE, BA VI, HANOI - Manh Hung, Bui; Thi Phuong Nhung, Vo; Thi Thanh, Dong (Journal of Forestry Science and Technology, 2018)
Households living in mountainous areas often have very particular characteristics. This household income is often dependent on forest resources. Ba Vi commune, Ba Vi district was the poorest commune in Hanoi city. This paper used correspondence analysis and comparative analysis method to analyze community characteristics of Ba Vi commune, used the multivariate regression model to analyze the contribution of agro-forestry activities to household income in the study area. The results showed that the community was mostly Dao ethnic group, had low education level and the households had well-off income usually did medicine profession. Agro-forestry activities contribute significantly household income in the study area. The results of the analysis show that the order of agro-forestry activities that bring income to households from high to low include: medical plants collection, grazing cattle, timber exploitation, shifting cultivation and intensive cultivation under the forest canopy. Based on the results of research, the paper proposed some solutions to improve household income in the study area.